Nonlinear flutter analysis of SMA fiber-reinforced composite panels under combined supersonic and thermal loads - Yang , Le; Han, Mingjun; Wang, Weidong (Archive of Mechanical Engineering, 2026)
The flutter of a shape memory alloy (SMA) fiber-reinforced panel in hypersonic flow is investigated. A nonlinear aerothermoelastic governing equation is formulated by coupling Von Kármán’s large deflection plate theory with first-order piston theory aerodynamics. Discretization via the Galerkin method enables the derivation of analytical solutions for the critical dynamic pressure and flutter frequency, using the Routh-Hurwitz criterion and Hopf bifurcation theory. Numerical integration confirms the predicted stability loss via a supercritical Hopf bifurcation, leading to limit cycle oscillations. The results demonstrate thatSMAfibers raise the flutter boundary through recovery stress and a high elastic modulus, which increase the equivalent structural stiffness –an effect that intensifies with SMA volume fraction. Conversely, aerodynamic heating induces thermal softening, creating a destabilizing thermomechanical feedback loop that reduces the stability margin. A nonlinear saturation effect is observed: beyond a critical fiber content, the marginal stability benefit diminishes. This suggests that strategically placing localized, high-concentration SMA fibers provides a mass-efficient strategy for significant stability enhancement.